2009
DOI: 10.1038/hdy.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of inbreeding depression among floral and fitness traits in Silene nutans

Abstract: The magnitude and variation of inbreeding depression (ID) within populations is important for the evolution and maintenance of mixed mating systems. We studied ID and its genetic variation in a range of floral and fitness traits in a small and large population of the perennial herb Silene nutans, using controlled pollinations in a fully factorial North Carolina II design. Floral traits and early fitness traits, that is seed mass and germination rate, were not much affected by inbreeding (do0.2). In contrast, '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
3
13
2
4
Order By: Relevance
“…d within populations can be affected by current and past (bottlenecks, founder effects and genetic drift) population size and genetic variation. It is expected to be lower in small than in large populations, and in populations with low than with high genetic variation (Mustajärvi et al, 2005;Hirayama et al, 2007;Thiele et al, 2010;Angeloni et al, 2011). In general, lower levels of d are expected in small populations with a long history of inbreeding because deleterious genes presumably have been purged from populations of selfers.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…d within populations can be affected by current and past (bottlenecks, founder effects and genetic drift) population size and genetic variation. It is expected to be lower in small than in large populations, and in populations with low than with high genetic variation (Mustajärvi et al, 2005;Hirayama et al, 2007;Thiele et al, 2010;Angeloni et al, 2011). In general, lower levels of d are expected in small populations with a long history of inbreeding because deleterious genes presumably have been purged from populations of selfers.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…In general, parameters not involved in fitness seem to be less affected by ID (DeRose and Roff, 1999). Thiele et al (2010) proposed the lower effect of ID in floral traits than in fitness traits could be because selection acts more strongly on flowers than on fitness or because selection acting on floral traits may be stabilizing, in contrast to selection on fitness traits that likely is directional. Indeed, previous studies showed ID has hardly any effect on flower size or on the floral pieces such as sepals or petals (Ellmer and Andersson, 2004;Thiele et al, 2010).…”
Section: Effect Of Id In the First Stages Of The Life Cycle Of Anagyrmentioning
confidence: 99%
“…They suggested that mixed mating (MM) in many species may represent transitional states or incidental by-products of other adaptive mechanisms Porcher et al, 2009;Busch et al, 2010). In contrast, increasing evidence suggests that MM is evolutionarily stable in seed plants (Goodwillie et al, 2005;Davis and Turner-Jones, 2008;Winn and Moriuchi, 2009;Thiele et al, 2010), even if they possess strong inbreeding depression (Goodwillie et al, 2005) or in obligately outcrossing species (Crawford et al, 2010).…”
Section: Evolutionary Controversy: Reproductivementioning
confidence: 99%
“…In natural populations, inbreeding depression often varies among different populations (Weber and Goodwillie, 2009), isolated patches within a population (Kolehmainen et al, 2010), individuals (Busch et al, 2010), life-cycle stages (Gonzalez-Varo and Traveset, 2010;Hirao, 2010), generations (Glaettli and Goudet, 2006;Ferriol et al, 2011), and stressful environmental conditions (Cheptou, 2006). This variation is important for the evolution and maintenance of MM systems (Thiele et al, 2010), and the relative composition of inbred and outbred plants, which in a natural population is determined directly by population selfing rate, substantially influences the magnitude of inbreeding depression (Cheptou and Schoen, 2007). For example, in the perennial herb Silene nutans (Caryophyllaceae), high inbreeding depression (δ > 0.5), representing multiplicative fitness at the population level, suggests that the MM system is not stable, but should evolve towards outcrossing; however, some paternal families had δ < 0.5, even in the cumulative relative fitness measure that suffered most from inbreeding depression (δ = 0.74).…”
Section: Inbreeding Depression Vs Self-evolutionmentioning
confidence: 99%
See 1 more Smart Citation